Mathematical literacy in pre-service teacher-designed mathematics comics - Zetra Hainul Putra; Gustimal Witri; Syahrilfuddin Syahrilfuddin (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
Mathematical literacy is a key point of the Program for International Student Assessment (PISA) study, and indeed it becomes a concern for some studies in many countries. This study aims at investigating mathematics literacy presented in mathematics comics, and it focuses on mathematical contexts and contents presented in thirteen pre-service teacher-designed mathematics comics. The findings show that personal is the most favourable contents, while quantity and change and relationships are mostly contexts chosen by the pre-service teachers in their designed mathematics comics. The implication of this study is that teacher-designed mathematics comics still emphasis on a daily life context that closed to students’ life.